Models of Hydro Power Plant in Dynamic Security Analyses of Electric Power Interconnections - Ivanović, Milan V; Popović, Dragan D.; Arnautović, Dušan; Bogdanović, Slobodan; Džepčeski, Dane; Dragosavac, Jasna; Pavlović, Jelena; Minić, Saša (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
This paper presents hydropower plant models used in dynamic security analyses of electric power interconnections. The general structure and functional block diagram of a hydropower plant are given, as well as a review of the current state of hydropower plants within the electrical power system of Serbia. A hydropower plant model used for analyses of short-term dynamics, where transient stability analyses are dominant, is presented. Additionally, a hydropower plant model used for the analyses of long-term dynamics is presented, providing insight into the role and effects of a hydropower plant, which would be included in the secondary and tertiary load-frequency control. Following verification based on experimental measurements, all these models have been incorporated into appropriate computer programs for dynamic security analyses of electric power interconnections. The computer programs mentioned have been developed at the Institute "Nikola Tesla" and some typical examples of their application have been provided.
Keywords: primary; secondary and tertiary load frequency control; short; mid and long-term dynamics; hydro power plant